Acetic Acid Causes Endoplasmic Reticulum Stress and Induces the Unfolded Protein Response in Saccharomyces cerevisiae - Kawazoe, Nozomi; Kimata, Yukio; Izawa, Shingo (Frontiers in Microbiology, 2017)
Since acetic acid inhibits the growth and fermentation ability of Saccharomyces cerevisiae, it is one of the practical hindrances to the efficient production of bioethanol from a lignocellulosic biomass. Although extensive information is available on yeast response to acetic acid stress, the involvement of endoplasmic reticulum (ER) and unfolded protein response (UPR) has not been addressed. We herein demonstrated that acetic acid causes ER stress and induces the UPR. The accumulation of misfolded proteins in the ER and activation of Ire1p and Hac1p, an ER-stress sensor and ER stress-responsive transcription factor, respectively, were induced by a treatment with acetic acid stress (> 0.2% v/v). Other monocarboxylic acids such as propionic acid and sorbic acid, but not lactic acid, also induced the UPR. Additionally, ire1∆ and hac1∆ cells were more sensitive to acetic acid than wild-type cells, indicating that activation of the Ire1p-Hac1p pathway is required for maximum tolerance to acetic acid. Furthermore, the combination of mild acetic acid stress (0.1% acetic acid) and mild ethanol stress (5% ethanol) induced the UPR, whereas neither mild ethanol stress nor mild acetic acid stress individually activated Ire1p, suggesting that ER stress is easily induced in yeast cells during the fermentation process of lignocellulosic hydrolysates. It was possible to avoid the induction of ER stress caused by acetic acid and the combined stress by adjusting extracellular pH.